1994
DOI: 10.1111/j.1365-2249.1994.tb06526.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of blood levels of IgM, IgA, IgG and IgG subclasses in Sudanese visceral leishmaniasis patients

Abstract: SUMMARYWe developed an ELISA test using leishmania antigenic extracts to detect anti gen-specific antibiidy responses, including subclass ;tnd isotype analysis, in visceral leishtnaniasis (VL) patients Prom Ihe Sudan. A total of ^2 parasitologicLtlly proven patients were cotnpared with cutaneous Icishmaniiisis. schistosomiasis, malaria, onchucerciasis and tuberculosis patients, as well as with healthy endemic and non-endemic controls. Some VL patients were exiimined before and alter chemotherapy. VL patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Several studies have demonstrated that high levels of parasite-specific IgG are generated during leishmaniasis (46,47). This is especially true with human visceral leishmaniasis in which rheumatoid factor (48 -50) and parasite-specific IgG levels are high (27)(28)(29)(30)(31)(32), making it more likely that amastigotes derived from lesions would be opsonized with host IgG. Our model would predict that disease exacerbation caused by immune complexes would only occur late in disease, after parasite-specific IgG was generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that high levels of parasite-specific IgG are generated during leishmaniasis (46,47). This is especially true with human visceral leishmaniasis in which rheumatoid factor (48 -50) and parasite-specific IgG levels are high (27)(28)(29)(30)(31)(32), making it more likely that amastigotes derived from lesions would be opsonized with host IgG. Our model would predict that disease exacerbation caused by immune complexes would only occur late in disease, after parasite-specific IgG was generated.…”
Section: Discussionmentioning
confidence: 99%
“…IgG Abs to Leishmania are prominent in human visceral leishmaniasis, and they are also produced in BALB/c mice during Leishmania infection (27)(28)(29)(30)(31)(32). The levels of IgG increase as disease progresses and parasites disseminate.…”
Section: Il-10 Reduces Ag Presentation and Either Inhibits Or Biases mentioning
confidence: 99%
“…Anam et al (144) also hinted at a possible (diagnostic) role for L. donovani-specific IgG3 antibody isotype detection. While the IgG3 antibody level decreases significantly posttreatment (148,149), the pharmacodynamic value of this marker is probably very low, as the time to normalcy for IgGs is longer than 3 months for both CL and VL patients (150)(151)(152)(153)(154).…”
Section: Identified Biomarkersmentioning
confidence: 99%
“…When antileishmanial antibody level was compared between children and adult samples of KA and PKDL sera, significantly elevated levels of IgG3 and IgG4 were evident in children cases compared to adult KA cases. Investigations of IgG subclass in Sudanese patients have shown maximum generation of IgG3 and IgG4 (35).…”
Section: Discussionmentioning
confidence: 99%